"Many and Dreadful Disasters": Mediterranean Travel, Plague, and Quarantine in the Late Eighteenth Century. Issue 1 (1st June 2021) - Walchester, Kathryn
Abstract: Our recent experiences of quarantine during the COVID-19 outbreak have exposed the vulnerability of poorer members of society and has highlighted their increased suffering during the period of restricted mobility. This article considers the way in which quarantine exacerbates inequalities from a historical perspective, looking at enforced periods of restricted travel and its impact on servants and lower-class British travelers of the eighteenth century in Europe. It examines both the history of representations of plague and contagion, and some of the human reactions to fears of disease, one of which was the imposition of quarantine measures. Three main sources are referred to: Patrick Brydone's A Tour through Sicily and Malta in a Series of Letters to William Beckford, published in 1790; Elizabeth, Lady Craven's "A Journey through the Crimea to Constantinople in a series of Letters, " published in 1789; and the unpublished letters of William Fletcher, manservant to Lord Byron, from his journeys in 1811. The texts produced by these travelers from the eighteenth century offer rich material for the consideration of the impact of mobility and immobility both of and on the body and how these experiences were strikingly different depending on the social class of the traveler.